SUSTAINABILITY: REVIEW OF THE LITERATURE AND GAP IN RESEARCH - Hemanth Goparaj,Radha. R. Sharma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Organizations play a significant role in the society. Organizations either produce goods or offer services by utilizing efforts and skills of people, living in a society, thus facilitating income generation and also reaping the profits. In this process, organizations are causing certain social problems by producing unsafe products, releasing industrial effluents in to environment thereby causing and increasing pollution and involving children in their work and exploiting child labor (Wood, 1991; Bertrand, 2010).